Pediatric dentistry approach in a child with Aicardi-Goutières Syndrome type 2: A case report and literature review - Melis Arda Sözüöz; Ezgi Aydın Varol; Merve Aksoy (Arbu Academic Publishing, 2024)
Aicardi-Goutières Syndrome is a rare autosomal recessive disorder characterized by a triad of partial or complete agenesis of the corpus callosum, infantile spasms, and chorioretinal lacunae. The condition predominantly affects females, as males often do not survive the embryonic period. Intellectual disability associated with the syndrome ranges from mild to moderate. There is limited information in the literature regarding the oral manifestations of this syndrome. This case report aims to provide insights into the development of primary dentition in patients with Aicardi-Goutières Syndrome and to raise awareness about the oral and dental health needs of these rare pediatric patients, particularly during early childhood. In this case report, it was observed that the primary teeth of a 2-year-5-month-old patient had not yet erupted. Notably, even at 3 years and 1 month old, the patient's primary dentition remained incomplete despite continued monitoring during follow-up examinations. These patients often have limited ability to cooperate with dental treatments due to their intellectual disability, which complicates the process. Furthermore, due to the respiratory risks associated with the syndrome, dental treatments under general anesthesia are generally not preferred. In this context, maintaining the oral health of these patients and implementing preventive strategies, including topical fluoridation, along with appropriate oral hygiene instructions and dietary modifications, are crucial in managing patients with Aicardi-Goutières Syndrome. Pediatric dentists are responsible for educating families on these matters, and caregivers play a vital role in maintaining the oral health of these patients by collaborating closely with dental specialists.